2005
DOI: 10.1007/s00535-004-1560-1
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins concordant for intestinal Behçet’s disease

Abstract: Although Behçet's disease (BD) is a multisystem disorder of unknown causes, both genetic and environmental factors have been suggested. This is the second reported case of monozygotic twins concordant for Behçet's disease and the first such report of intestinal Behçet's disease. Patient 1 was a 17-year-old man with fever, recurrent oral aphthae, and skin eruptions. He developed hematochezia and was given corticosteroid empirically. One month after he was discharged, he again developed oral ulcerations, fever, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
10
0
7
Order By: Relevance
“…The disease in parents significantly influences the risk of RAS and the course of the condition in their children—patients with a positive family history of RAS suffer more frequent recurrences and more severe course of the disease comparing to those with a negative RAS family history (Almoznino et al 2013; Lehner 1978; Yilmaz and Cimen 2010). Moreover, in both, RAS and Behçet's syndrome, the risk of the disease development was higher in monozygotic twins than in dizygotic ones (Kobayashi et al 2005; Yilmaz and Cimen 2010). The genetic risk factors that modify the individual susceptibility to RAS include various DNA polymorphisms distributed in the human genome, especially those related with the alterations in the metabolism of interleukins (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12), interferon (IFN)-γ and tumor necrosis factor (TNF)-α (Akman et al 2006, 2008; Bazrafshani et al 2002, 2003; Buño et al 1998; Guimarães et al 2006, 2007; Hall et al 2000; Kalkan et al 2013; Pekiner et al 2012).…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…The disease in parents significantly influences the risk of RAS and the course of the condition in their children—patients with a positive family history of RAS suffer more frequent recurrences and more severe course of the disease comparing to those with a negative RAS family history (Almoznino et al 2013; Lehner 1978; Yilmaz and Cimen 2010). Moreover, in both, RAS and Behçet's syndrome, the risk of the disease development was higher in monozygotic twins than in dizygotic ones (Kobayashi et al 2005; Yilmaz and Cimen 2010). The genetic risk factors that modify the individual susceptibility to RAS include various DNA polymorphisms distributed in the human genome, especially those related with the alterations in the metabolism of interleukins (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12), interferon (IFN)-γ and tumor necrosis factor (TNF)-α (Akman et al 2006, 2008; Bazrafshani et al 2002, 2003; Buño et al 1998; Guimarães et al 2006, 2007; Hall et al 2000; Kalkan et al 2013; Pekiner et al 2012).…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…Few cases of familial intestinal BD have been reported to date, suggesting the contribution of genetic factors in its pathogenesis [24, 25]. Recently, genome-wide association studies (GWAS) have identified several genes associated with susceptibility to BD including the interleukin (IL)-23R, IL-10, STAT, and HLA-B51 genes [2629].…”
Section: Pathogenesis Of Intestinal Bdmentioning
confidence: 99%
“…The higher concordances for BD in monozygotic twins compared with dizygotic twins suggests genetic predisposition [43]. In addition, there are two reports of monozygotic twins concordant for BD [43, 44]. In one of these twins reports both patients interestingly showed intestinal BD; however, they were HLA-B51 negative [44].…”
Section: Familial Aggregationmentioning
confidence: 99%
“…In addition, there are two reports of monozygotic twins concordant for BD [43, 44]. In one of these twins reports both patients interestingly showed intestinal BD; however, they were HLA-B51 negative [44]. In the other report, the twin brothers were both HLA-B51 positive and developed the disease at the same age [45].…”
Section: Familial Aggregationmentioning
confidence: 99%